Comparing smoking and smoking cessation process in the Republic of Karelia, Russia and North Karelia, Finland. Issue 9 (1st September 1999) - Laatikainen, T; Vartiainen, E; Puska, P
Abstract : STUDY OBJECTIVE: The aims of this study were to assess and validate self reported smoking prevalence and to assess smoking cessation related process variables in the Republic of Karelia, Russia and in North Karelia, Finland. DESIGN: Comparative population surveys of random population samples from both areas in spring 1992. The study included a self administered questionnaire, physical measurements and laboratory tests. The validity of self reported smoking prevalence was assessed by serum cotinine analyses. SETTING: The district of Pitkäranta in the Republic of Karelia, Russia and province of North Karelia, Finland. PARTICIPANTS: The study population was a 25 to 64 year old population in both areas. A stratified random sample of 1000 people in Pitkäranta and 2000 people in North Karelia was drawn from the population registers. In Pitkäranta 380 men and 455 women, and in North Karelia 673 men and 803 women, participated in the survey. RESULTS: The self reported prevalence rates of daily smoking in Pitkäranta were 65% among men and 10% among women. In North Karelia the respective rates were 29% and 13%. Women in Pitkäranta greatly underreported their smoking status, which was assessed by comparing the self reported data to the serum cotinine measurements. The smoking prevalence among women in Pitkäranta would rise from 10% to 21% if all participants with high cotinine values would be regarded as smokers. Compared with smokers in North Karelia, a higher percentage of smokers in Pitkäranta expressed their wish to quit and believed that they would succeed. However, on average they had fewer previous smoking cessation attempts than smokers in North Karelia. In addition, the health personnel in North Karelia were more active in advising smokers to quit. CONCLUSIONS: High smoking prevalence among men in Pitkäranta obviously contributes much to the high premature death rate in the Republic of Karelia. There is considerable underreporting of smoking in Pitkäranta, especially among women, which is probably attributable to the cultural unacceptability of female smoking in Russia. The common wish to quit, few previous cessation attempts and much lower rates of ex smokers, together with less smoking cessation counselling from health personnel, need to be considered in tailoring antismoking interventions in the area.